Validation of different PSMA-PET/CT-based contouring techniques for intraprostatic tumor definition using histopathology as standard of reference. (December 2019) - Zamboglou, Constantinos; Fassbender, Thomas F.; Steffan, Lina; Schiller, Florian; Fechter, Tobias; Carles, Montserrat; Kiefer, Selina; Rischke, Hans C.; Reichel, Kathrin; Schmidt-Hegemann, Nina-Sophie; Ilhan, Harun; Chirindel, Alin F.; et al.
Highlights: Different teams delineated [68Ga]-PSMA-11-PET images of prostates with proven prostate cancer. Regions with high tracer-uptake were highly specific for PCa and should be used for biopsy guidance. Both manual and semi-automatic delineation approaches may provide high sensitivity. Sensitive GTV delineation provides a useful base for focal therapy approaches. Abstract: Purpose: Accurate definition of the intraprostatic gross tumor volume (GTV) is crucial for diagnostic and therapeutic approaches in patients with primary prostate cancer (PCa). The optimal methodology for contouring of GTV using Prostate specific membrane antigen positron emission tomography (PSMA-PET) information has not yet been defined. Methods and Materials: PCa patients who underwent a [68Ga]PSMA-11-PET/CT followed by radical prostatectomy were prospectively enrolled ( n  = 20). Six observer teams with different levels of experience and using different PET image scaling techniques performed manual contouring of GTV. Additionally, semi-automatic segmentation of GTVs was performed using SUVmax thresholds of 20–50%. Coregistered histopathological gross tumor volume (GTV-Histo) served as reference. Inter-observer agreement was assessed by calculating the Dice similarity coefficient (DSC). Results: Most contouring methods provided high sensitivity and specificity. For manual delineation, scaling the PET images from SUVmin-max: 0–5 resulted in high sensitivity (>86%). The highest specificity (100%) was obtained by scaling the PET images from SUVmin-max: 0-SUVmax. High interobserver agreement (median DSC 0.8) was observed when using the same PET image scaling technique (PET images SUVmin-max: 0–5). For semi-automatic segmentation, a low SUVmax threshold of 20% optimized sensitivity (SUVmax threshold 20%, 100% sensitivity, 32% of prostatic volume), whereas a higher threshold optimized specificity (SUVmax threshold 40%–50%, 100% specificity). Conclusions: Contouring of regions with high tracer-uptake resulted in very high specificities and should be used for biopsy guidance. Both manual and semi-automatic approaches using validated SUV scaling (SUVmin-max: 0–5) or thresholding (20%) may provide high sensitivity, and should be considered for PSMA-PET-based focal therapy approaches.